Masa Inkubasi Gejala Penyakit Hawar Daun Tanaman Kentang yang Diinduksi Ketahanannya oleh Jamur Antagonis Trichoderma viride - Purwantisari, Susiana; Priyatmojo, Achmadi; Sancayaningsih, Retno Peni; Kasiamdari, Rina Sri (Bioma : Berkala Ilmiah Biologi, 2016)
Late blight disease caused by Phytophthora infestans, is probably the single most important disease of potatoes worldwide. Infected plants were quickly killed and were difficult for replanting, causing significant losses for the growers. Various control methods were examined including the use of biocontrol agents of Trichoderma spp. The biocontrol potential of Trichoderma viride against potato late blight pathogen, Phytophthora infestans, were studied under greenhouse conditions. The research objective was to determine the ability of biocontrol agents Trichoderma viride to delay late blight disease incidence on potato plants in the field. The in vivo experiment was carried out at potato land area located at BALITSA in Cikole Sub District, Lembang District and Bandung Regency. Completely Randomized Design was used with six treatment and five replicates. The treatment tested consist of control (without pathogen fungal and antagonists fungus application too), control (with pathogen fungal application and without antagonist fungal application), chemical fungicide application, antagonist fungal application 2 weeks before planting, application 1 week after planting and both application 2 weeks before and 1 week after planting. Result of the research showed that application of antagonists fungal could delay disease intensity until 14 days. These antagonist could be used as biological agents initials to control leaf blight disease. Key words: Biological control, Potato late blight, Phytophthora infestans, Trichoderma viride